Estudio de la reputación online de la Gobernación Provincial de Chimborazo 2021. - Tagua Reino, Mishell Estefanía (2023)
The present research is intended to conduct a study on the online reputation of the Provincial Government of Chimborazo, between the months of July and December 2021, whose main analysis is based on the social network Facebook, as it is a digital platform of great interaction in government institutions nowadays. The methodology employed was of mixed type, which allowed to know data and results of valuation made by users of the Governorate of Chimborazo. The research is non-experimental because data was observed, analyzed, and collected without any type of manipulation of the information obtained. The main technique was content analysis and a structured matrix was used, in which the data obtained were classified by month, date, time of publication, topic, content production, message format, type of publication, interactions, type of comments, and interaction; on the other hand, interviews were conducted with the use of a structured questionnaire that was applied both to the person in charge of the Communication Department of the Governorate of Chimborazo and two experts in corporate communication. A total of 170 publications were analyzed in the respective period, most of which were related to the health situation because the country was in a health emergency due to COVID-19. Within the analysis carried out, the types of comments were established, whether in favor, against, or neutral, establishing the results in their respective percentages, which led to the conclusions and recommendations. Finally, a proposal was developed to improve the image on the social network Facebook, in order to establish an adequate online reputation for the institution, through the application of communication criteria appropriate to the governmental organization.